Banking services in Portugal: a preliminary analysis to the perception and expectations of front office employees - Ramos, J.; Ferreira, F.; Barata, J. M. M. (International Journal of Management and Enterprise Development, 2011)
The banking sector offers high rates of employment in Portugal. This study aims to determine the degree of satisfaction and career expectations of bank branch employees in the Portuguese region of Santarem to inform graduated students who search for job opportunities and professional careers in the banking sector. It should be highlighted that the region of Santarem has been selected based on reasons of convenience. In terms of empirical results, a questionnaire has been developed and it should be mentioned that the degree of satisfaction has been considered as high, i.e. despite the effects of several variables, such as the strategic impact of information and communication technologies, bank branch employees revealed themselves to be optimistic about their future and generally satisfied with their job positions.